Psycopathological Discourse and Contemporary Subjectivity - Aceituno M., Roberto; Bornhauser, Niklas (Revista de Psicología, 2005)
In this paper we present a discussion about the relation between the discourse of clinical psychology (psychology, psychiatry, psychotherapy) and /contemporary subjectivity. We could define clinical discourse as a set of practices and knowledge applied to psychic disorders or, in a roader sense, to the area of mental health. The term discourse suggests that these practices are formed in the historical and sociocultural framework that defines its knowledge and application conditions. On the other hand, contemporary subjectivity is understood as the dynamics and subjective structures which are typical of these current times, in the framework of the sociocultural conditions of the so called late modernity or postmodernity. The analysis is focused on borderline disorders as a discursive expression of the contemporary subjectivity.